Full-season and post-harvest applications of sterol-inhibiting fungicides to reduce ascospore formation in Venturia inaequalis - Biggs, A.R.; Warner, J. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 1990)
Several sterol-inhibiting (SI) fungicides were tested in post-harvest and full-season spray programs for the inhibition of ascospore formation by Venturia inaequalis, the causal fungus of apple scab. Post-harvest treatments with flusilazole and diniconazole were comparable to or better than those with benomyl and suppressed ascospore production by 55 to 90 %, although bitertanol stimulated ascospore production by up to 52 %. When applied nine times in full-season programs, bitertanol, flusilazole, and triflumizole reduced ascospore formation to a degree similar to or greater than that achieved with dodine. Full-season programs with SI fungicides in combination with mancozeb were highly effective for reducing ascospore production.